Integrating the ‘Snakes and Ladders’ Board Game with Collaborative Learning to Enhance Young Learners’ Vocabulary - Putri Sonya Artaninda; Arso Setyaji; Ririn Ambarini (English Learning Innovation, 2025)
Learning vocabulary is considered the most important component in mastering English, especially for students at the elementary school level who are young learners. However, many students often have difficulty pronouncing English words, making it difficult to memorize English vocabulary. In addition, students easily feel bored when learning vocabulary, so creative and innovative learning is needed to create students' interest in attending vocabulary classes. The traditional game 'Snakes and Ladders' has been innovatively adapted to create an engaging learning experience to improve vocabulary skills. This study explores the effectiveness of integrating the 'Snakes and Ladders board game with collaborative learning strategies to enhance vocabulary acquisition among students at SDN Getasblawong through the Kampus Mengajar 6 program. The quantitative method with pre-experimental design. The findings indicate a significant improvement in vocabulary acquisition among students who participated in the game-based learning activities compared to those who did not. This study highlights the potential of integrating traditional board games with collaborative learning strategies to create innovative and effective learning environments. The findings contribute to the growing body of literature on gamified learning approaches and provide practical insights for educators seeking to enhance vocabulary acquisition in elementary school settings.